Exploring the Molecular Mechanisms Underlying the Protective Effects of Microbial SCFAs on Intestinal Tolerance and Food Allergy - Luu, Maik; Monning, Heide; Visekruna, Alexander (Frontiers in Immunology, 2020)
A body of evidence suggests that food allergy (FA) has increased in prevalence over the past few decades. Novel findings support the hypothesis that some commensal bacteria and particularly microbial metabolites might contribute to development of oral tolerance and prevention from FA. Recently, beneficial effects of short-chain fatty acids (SCFAs), the main class of gut microbiota-derived metabolites, on FA have been proposed. The intestinal SCFAs are major end products during bacterial fermentation of complex and non-digestible carbohydrates such as dietary fiber. The multifaceted mechanisms underlying beneficial effects of SCFAs on the mucosal immune system comprise the regulation of diverse cellular pathways in epithelial, dendritic and T cells, as well as the impact on the immunometabolism and epigenetic status of regulatory lymphocytes. Of note, SCFAs are effective inhibitors of histone deacetylases (HDACs). As a consequence, SCFAs appear to be implicated in attenuation of intestinal inflammation and autoimmune diseases. In this review, we will discuss the recent development in this research area by highlighting the role of the individual SCFAs acetate, propionate, butyrate and pentanoate in promoting the differentiation of regulatory T and B cells and their potential beneficial effects on the prevention of FA. In this context, targeted alterations in the gut microbiota in favor of SCFA producers or supplementation of medicinal food enriched in SCFAs could be a novel therapeutic concept for FA.